The Structural Evolution of Galaxies at z < 7 - Whitney, Amy (2021)
This thesis utilises all five fields of the CANDELS survey to probe galaxy evolution out to redshift z ∼ 7 in the context of size, surface brightness, and structure. Both the optical and ultraviolet (UV) rest-frames are used depending on the context.